2005
DOI: 10.1523/jneurosci.1311-05.2005
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Investigation of Connections of the Prefrontal Cortex in the Human and Macaque using Probabilistic Diffusion Tractography

Abstract: The functions of prefrontal cortex (PFC) areas are constrained by their anatomical connections. There is little quantitative information about human PFC connections, and, instead, our knowledge of primate PFC connections is derived from tracing studies in macaques. The connections of subcortical areas, in which white matter penetration and hence diffusion anisotropy are greatest, can be studied with diffusion-weighted imaging (DWI) tractography. We therefore used DWI tractography in four macaque and 10 human h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

34
319
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 380 publications
(354 citation statements)
references
References 94 publications
(143 reference statements)
34
319
0
1
Order By: Relevance
“…S2 and S3) was consistent with the segmentation pattern reported in previous studies (Cohen et al, 2009;Croxson et al, 2005;Lehericy et al, 2004;Voorn et al, 2004), which confirmed the probabilistic tracking process of diffusion tensor images in the present study.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…S2 and S3) was consistent with the segmentation pattern reported in previous studies (Cohen et al, 2009;Croxson et al, 2005;Lehericy et al, 2004;Voorn et al, 2004), which confirmed the probabilistic tracking process of diffusion tensor images in the present study.…”
Section: Resultssupporting
confidence: 92%
“…Images in the MNI standard space were entered into general linear models (GLMs) for voxel-wise analyses. The method has been well validated and used in diffusion tensor imaging studies (Cohen et al, 2009;Croxson et al, 2005;Johansen-Berg and Rushworth, 2009). …”
Section: Image Preprocessingmentioning
confidence: 99%
“…Recently, the use of areal connections to define areas has been employed in humans. Diffusion tensor imaging (DTI) tractography, which measures the directional diffusion of water within a voxel, can reveal local anisotropic differences in fiber bundles in neighboring regions of cortex in living humans, and was recently used to delineate some human cortical areas Croxson et al, 2005;Johansen-Berg et al, 2004;Johansen-Berg et al, 2005;Klein et al, 2007). The use of probabilistic fiber bundle differences in diffusion tractography is in some respects analogous to the use of blunt dissection to identify major fiber bundles in humans.…”
Section: Imaging and Functional Areasmentioning
confidence: 99%
“…The prefrontal cortex (PFC), which includes the dorsolateral prefrontal cortex (DLPFC), orbital frontal cortex (OFC) and the inferior frontal cortex (IFC), plays a central role in executive functioning through its influence on subcortical and posterior cortical regions via extensive anatomical connections to these areas (Croxson et al, 2005;Leh et al, 2007). Recent evidence suggests that successful response inhibition is mediated through striatal dopamine receptors in this frontal-striatal circuit (Ghahremani et al, 2012), and that increased activation of this network is associated with improvement in response-inhibition performance (Congdon et al, 2010).…”
Section: Introductionmentioning
confidence: 99%